Efficiency of Bank-Linked Zakat Institutions in Indonesia: A DEA Approach - Nisak, Khoirun; Najib, M. Thoha Ainun; Setyowati, Endah (El-Barka, 2025)
The remarkable potential of zakat in Indonesia has not been fully realized due to an optimal collection rate, necessitating more efficient management. One strategic step is the integration of zakat institutions with banking to leverage the network, technology, and governance of banks in enhancing the collection and distribution of zakat. However, the efficiency performance of zakat institutions affiliated with banks is still rarely studied using a quantitative approach. This study aims to measure the efficiency of zakat management institutions affiliated with banks in Indonesia and compare their performance using the Data Envelopment Analysis (DEA) method. This research utilizes data from the period 2017–2023, with the unit of analysis being two bank zakat institutions: Baitul Maal Muamalat (BMM) and YBM BRILiaN. Input variables include annual salaries, operational costs, and socialization costs, while output variables consist of collected and distributed zakat funds. The analysis was conducted using the DEA BCC (Banker, Charnes, Cooper) and CCR (Charnes, Cooper, Rhodes) models to identify technical and scale efficiency. The research results show that Baitul Maal Muamalat (BMM) was only at an optimal efficiency level during the 2017–2019 period, while its performance declined in the 2020–2022 period. On the other hand, YBM BRILiaN consistently achieved full efficiency throughout 2021–2023. These findings provide an empirical basis for managerial improvements and the strengthening of the capacity of bank zakat institutions, while also reinforcing the integration of zakat with the banking system in Indonesia.